Dashat Kitchen Financial Management For Stunting Prevention Case Study of Dashat Kitchen Sauyunan Pasir Impun Village, Mandalajati District, Bandung City - Setiawan, Iwan; Hamid, Edih Abdul; Nurohmat, Asep Gema; Diyaulhaq, Daffa Aulia (Amkop Management Accounting Review (AMAR), 2025)
In Indonesia, stunting is still a serious problem, especially in areas with limited access to nutrition and health services. One of the innovative efforts to tackle stunting is through the establishment of Healthy Kitchen to Overcome Stunting (Dashat), a community-based nutrition intervention program that focuses on providing nutritious food for at-risk families. Dashat kitchen (Healthy Kitchen to Overcome Stunting) is an initiative from BKKBN that aims to overcome stunting by providing nutritious food for vulnerable groups. The implementation of financial management is the main key in ensuring the sustainability and efficiency of this program. Community Service aims to analyze the application of financial management in the operations of Dapur Dashat and how it contributes to the success of the program. The method used is a qualitative approach through in-depth interviews, field observations, and document analysis at the Dashat Kitchen Sauyunan, Pasir Impun Village, Mandalajati District, Bandung City. The results of this study show that good financial management including budget planning, transaction recording, and transparent reporting has an important role in ensuring program sustainability. The involvement of cadres and the community in fund management increases the sense of belonging and accountability. However, obstacles were also found such as low financial literacy and the lack of use of recording technology. Therefore, training and assistance in financial management aspects are important strategies to strengthen the effectiveness of Dashat as a local solution in stunting prevention. With an organized financial system, Dashat kitchen has the potential to become a model of sustainable and replicative community empowerment. The implementation of effective financial management has been proven to increase operational efficiency and strengthen public trust. The novelty of this study is the integration of financial management and nutrition interventions, community-based approaches, specific local contexts, evaluation of operational effectiveness and efficiency.